Comparison of 3- and 20-Gradient Direction Diffusion-Weighted Imaging in a Clinical Subacute Cohort of Patients with Transient Ischemic Attack: Application of Standard Vendor Protocols for Lesion Detection and Final Infarct Size Projection - Havsteen, Inger; Ovesen, Christian; Willer, Lasse; Nybing, Janus Damm; Ægidius, Karen; Marstrand, Jacob; Meden, Per; Rosenbaum, Sverre; Folke, Marie Norsker; Christensen, Hanne; Christensen, Anders (Frontiers in Neurology, 2017)
Objective: Diffusion tensor imaging may aid brain ischemia assessment, but is more time-consuming than conventional diffusion-weighted imaging (DWI). We compared 3- (3DWI) and 20-gradient direction DWI (20DWI) standard vendor protocols in a hospital-based prospective cohort of patients with transient ischemic attack (TIA) for lesion detection, lesion brightness, predictability of persisting infarction and final infarct size. Methods: We performed 3T-magnetic resonance imaging including diffusion and T2-fluid attenuated inversion recovery (FLAIR) within 72 hours and 8 weeks after ictus. Qualitative lesion brightness was assessed by visual inspection. We measured lesion area and brightness with manual regions of interest and compared with homologous normal tissue. Results: 117 patients with clinical TIA showed 78 DWI lesions. 2 lesions showed only on 3DWI. No lesions were uniquely 20DWI positive. 3DWI was visually brightest for 34 lesions. 12 lesions were brightest on 20DWI. The median 3DWI lesion area was larger for lesions equally bright, or brightest on 20DWI (median (IQR) 39 (18 - 95) versus 18 (10 - 34) mm2, P = 0.007). 3DWI showed highest measured relative lesion signal intensity (median (IQR) 0.77 (0.48-1.17) versus 0.58 (0.34-0.81), P = 0.0006). 3DWI relative lesion signal intensity was not correlated to absolute signal intensity, but 20DWI performed less well for low-contrast lesions. 3DWI lesion size was an independent predictor of persistent infarction. 3-gradient direction apparent diffusion coefficient areas were closest to 8-week FLAIR infarct size. Conclusion: 3DWI detected more lesions and had higher relative lesion signal intensity than 20DWI. 20DWI appeared blurred, and did not add information. Clinical Trial Registration: http://www.clinicaltrials.gov. Unique Identifier NCT01531946.